Teaching deaf/hard of hearing children in the modern-day classroom. A teacher’s experience of inclusion with deaf/hard of hearing children in the mainstream classroom. - Farrell, Teresa (Trinity College (Dublin, Ireland). School of Education, 2021)
This research is going to explore is the area of deaf/hard of hearing children in a range of mainstream classroom settings. Recently the Irish Sign Language Act was passed in the Dáil, in which the aim of the act was equality for deaf people in Ireland. The act mainly focuses on the area of services for deaf people and fails to mention the area of education. This area will explore teachers' experience teaching D/HH children and how they include deaf children in the mainstream classroom. It will give an insight to teachers’ pedagogy surrounding D/HH children. It will display the challenges that teachers face when trying to teach and communicate with deaf children in their classroom and the challenges the D/HH students faced when communicating with their peers. Teachers will give their advice to future teacher who will have deaf children in their classrooms.
Keywords: Special Education; Education